Impact of oestrus synchronization devices on ewes vaginal microbiota and artificial insemination outcome - Reinoso-Peláez, Edgar L.; Saura, María; González-Recio, Óscar; González, Carmen; Fernández, Almudena; Peiro-Pastor, Ramón; López-García, Adrián; Saborío-Montero, Alejandro; Calvo, Jorge H.; Ramón, Manuel; Serrano, Malena (Frontiers in Microbiology, 2023)
The low pregnancy rate by artificial insemination in sheep represents a fundamental challenge for breeding programmes. In this species, oestrus synchronization is carried out by manipulating hormonal regimens through the insertion of progestogen intravaginal devices. This reproductive strategy may alter the vaginal microbiota affecting the artificial insemination outcome. In this study, we analysed the vaginal microbiome of 94 vaginal swabs collected from 47 ewes with alternative treatments applied to the progesterone-releasing intravaginal devices (probiotic, maltodextrin, antibiotic and control), in two sample periods (before placing and after removing the devices). To our knowledge, this is the first study using nanopore-based metagenome sequencing for vaginal microbiome characterisation in livestock. Our results revealed a lower abundance of the genera Oenococcus (Firmicutes) and Neisseria (Proteobacteria) in pregnant compared to non-pregnant ewes. We also detected a lower abundance of Campylobacter in the group of samples treated with the probiotic. Although the use of probiotics represents a promising practice to improve insemination results, the election of the suitable species and concentration requires further investigation. In addition, the use of progestagen in the synchronization devices seemed to increase the alpha-diversity and decrease the abundance of harmful microorganisms belonging to Gammaproteobacteria and Fusobacteriia classes, suggesting a beneficial effect of their use.